THE USE OF VIDEO BROADCAST IN TEACHING LISTENING-SPEAKING - Floriasti, Tri Wahyuni; Suciati, Suciati (Diksi, 2019)
(Title: The Use of Video Broadcast in Teaching Listening-Speaking). The latest technology, which comes like storm, gives us extra help in revealing the unseen that is beyond our reach and touch the untouchable in our hands. The technology gives us potential to do things we haven't been able to do before. One of the greatest challenges to the classrooms of today is mobile technology. As teachers, it's our job to make sure that students who are considered as digital natives learn through the omnipresence of the mainstream media. The world around us is changing in terms of communication and interaction that affect the way people see, think and learn the present environment, and connect with others. In education, we have three options when dealing with these changes: avoid it, struggle with it, or embrace it. It is our duty to prepare and adjust the classroom of today ready for tomorrow. Thus, this writing attempts to review the new trend in technology, the use of video broadcasting in teaching listening-speaking.Keywords: listening-speaking, video broadcasting, media